Estimation of the radon production rate in granite rocks and evaluation of the implications for geogenic radon potential maps: A case study in Central Portugal. (January 2017) - Pereira, A.; Lamas, R.; Miranda, M.; Domingos, F.; Neves, L.; Ferreira, N.; Costa, L.
Abstract : Abstract The goal of this study was to estimate radon gas production rate in granitic rocks and identify the factors responsible for the observed variability. For this purpose, 180 samples were collected from pre-Hercynian and Hercynian rocks in north and central Portugal and analysed for a) 226 Ra activity, b) radon ( 222 Rn) per unit mass activity, and c) radon gas emanation coefficient. On a subset of representative samples from the same rock types were also measured d) apparent porosity and e) apparent density. For each of these variables, the values ranged as follows: a) 15 to 587 Bq kg −1, b) 2 to 73 Bq kg −1, c) 0.01 to 0.80, d) 0.3 to 11.4 % and e) 2530 to 2850 kg m −3 . Radon production rate varied between 40 to 1386 Bq m −3  h −1 . The variability observed was associated with geologically late processes of low and high temperature which led to the alteration of the granitic rock with mobilization of U and increase in radon 222 Rn gas emanation. It is suggested that, when developing geogenic radon potential maps, data on uranium concentration in soils/altered rock should be used, rather than data obtained from unaltered rock. Highlights: The new dataset about the main control variables on radon emanation. The impact of the secondary processes (low and high temperatures) in radon emanation. The importance of the apparent porosity in the radon production rate. The implications of the results to the development of geogenic radon potential maps.